Cryptocurrency Taxation Features: International Experience for Sustainable Development of Ukraine’s Tax Sphere - Andrushchenko, Igor; Oksin, Vitaliy; Drozd, Serhii; Zaikina, Hanna; Frantovskyi, Yevhenii (European Journal of Sustainable Development, 2025)
The article is devoted to the analysis of the international experience of ?ryptocurrency taxation. The research methodology includes the use of general scientific and special methods of scientific knowledge, including dialectical, formal and logical, hermeneutics, generalization, comparison, analysis, synthesis, generalization, etc. It is noted that the tax systems of most countries of the world were not ready for were not ready for cryptocurrencies to come into circulation. Therefore, its non-recognition by individual states is associated with insufficient legal protection and impossibility of regulation in the tax field. This study is based on the experience of introducing cryptocurrency of such countries as Singapore, Australia, Greece, Brazil and New Zealand. Special attention is paid to the legislative consolidation of cryptocurrency in the indicated countries. The authors highlight various methods of cryptocurrencies taxation used in the countries under consideration, and their effectiveness in the tax area. The conclusion on the need to harmonize international approaches to cryptocurrencies taxation and develop global standards ensuring its effective regulation is made. Key words: digital assets, cryptocurrency, electronic money, tax system, legal status, declaration